MANAGEMENT OF CORNEAL ULCER PRESENTED WITH RARE PATHOGEN : STREPTOCOCCUS MITIS: Poster Presentation - Case Report - Resident - Ibnu Gilang Syawali; Marina Yusnita Albar (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal ulcers can arise from various corneal diseases, including infections, inflammation, and autoimmune disease. Staphylococcus aureus is the most common bacterial pathogen, but lesser- known bacteria like Streptococcus mitis can also cause corneal ulcers. Accurate diagnosis and treatment are essential to prevent vision loss and complications. Case Illustration : A 19-year-old female patient presented with a chief complaint of white spots on her right eye for three months. Previously, her right eye was hit by a foreign object and subsequently, the patient experienced redness and pain in the affected eye. One week later, white spot appeared in the patient's eye and reported to enlarge in the last month. The patient also complained of pain, blurry vision with visual acuity of 1/300, redness, glare, and a foreign body sensation. Corneal swab culture discovered Streptococcus mitis to be the causative agent. The patients was given hourly drop of topical levofloxacin. One month after initial treatment, patient’s symptoms was improving with visual acuity of 6/60 on her affected eye and the ulcer was healed. Discussion : Streptococcus mitis is a commensal pathogen in oral cavity and not normally cause infection of ocular tissue. It may cause ulcer due to prolonged use of topical steroid and previous ocular trauma, since Streptococcus mitis had low virulence rate. Conclusion : Corneal scraping culture should be carried out before treatment of infectious corneal ulcer. Streptococcus mitis is considered rare for corneal ulcer pathogen. Topical quinolones are the first- line drug for bacterial corneal ulcer and worked exceptional for wide range of bacteria.